Politicization of Identity in Local Election As A Soft Security Threat: A Case of 2017 Jakarta Gubernatorial Election - Putri Ariza Kristimanta; Mouliza Kristhopher Donna Sweinstani (Journal of Indonesian Social Sciences and Humanities, 2018)
The background of this study is the DKI Jakarta 2017 local election, which was followed by a series of demonstration and identity politicization against the prospective candidate from minority groups. A similar pattern had been applied in 2018 local election and 2019 national election where SARA (shortened from Suku, Agama, Ras, dan Antar-golongan or ethnicity, religion, race, and intergroup relations) is used to mobilize voters through black and negative campaigns. This study aims to explore how the politicization of identity in the DKI Jakarta Gubernatorial Election 2017 can be a soft security threat to human and societal security. By conducting literature studies to related documents, the authors conclude that what happened in DKI Jakarta is categorized as politicized collective identity. The results of the study describe that politicization of identity could cause three effects that can threaten security, namely (1) increasing negative sentiment towards minority groups; (2) increasing the number of cases of persecution and discrimination in the name of religion or ethnicity; and (3) causing community polarization on social media. The study recommends to the government to strengthen national identity, which involves all components of the state and society so that the issue of identity will not be shifted for negative connotation of short-term electoral agenda.